2019
DOI: 10.3390/nu11112790
|View full text |Cite
|
Sign up to set email alerts
|

Soy Products Ameliorate Obesity-Related Anthropometric Indicators in Overweight or Obese Asian and Non-Menopausal Women: A Meta-Analysis of Randomized Controlled Trials

Abstract: Background: The effect of soy products on the weight of overweight or obese people is controversial, so we aimed to conduct a systematic review and a meta-analysis of published randomized controlled trials to analyze whether supplementation with soy products can help them to lose weight. Methods: The relevant data before January 2019 in PubMed, Embase and Cochrane Library were searched. A random-effect model was adopted to calculate the weighted average difference of net changes of body weight, body mass index… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
36
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 81 publications
(67 reference statements)
2
36
1
Order By: Relevance
“…Suh and Lee (2005) found that there were no differences in the thickness of triceps, suprailiac, and thigh skinfold between the high-protein diet with exercise and the exercise-only groups after the intervention period of 8 weeks [51]. A meta-analysis stated that ISP can prevent fat accumulation and ameliorate anthropometric indicators in women [52], and our study supports these concepts. The results of this study showed that no significant differences were noticed in the improvements of skinfold thickness between the AET and AET + ISP groups (Table 4).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Suh and Lee (2005) found that there were no differences in the thickness of triceps, suprailiac, and thigh skinfold between the high-protein diet with exercise and the exercise-only groups after the intervention period of 8 weeks [51]. A meta-analysis stated that ISP can prevent fat accumulation and ameliorate anthropometric indicators in women [52], and our study supports these concepts. The results of this study showed that no significant differences were noticed in the improvements of skinfold thickness between the AET and AET + ISP groups (Table 4).…”
Section: Discussionsupporting
confidence: 79%
“…The results of our study are consistent with these reports. We found that AET combined with ISP supplementation improved the body weight, BMI, PBF, and PLBM more effectively than AET alone (all effect sizes > 0.8, Table 3), which may be related to the sustained decrease in appetite, enhanced satiety, and energy expenditure, and promotion of lipid metabolism due to the regulation of the expression of sterol regulatory element-binding proteins after ISP intake [7,13,52]. These findings indicate that ISP is an effective postexercise supplementation that can induce positive improvements in the body composition of women.…”
Section: Discussionmentioning
confidence: 88%
“…The average body weight of 66.69+9.44 kg of volunteers of age-group 20-59 years was found more in the routine diet group but was 59.88 + 10.47 kg and less after 60 days feeding of soybean added diet. A meta-analysis report of Mu et al, (14) confirmed that certain products of soy significantly (p<0.05) declined body weight of Asian populations (−0.37 kg).…”
Section: Discussionmentioning
confidence: 88%
“…The average BMI of volunteers in this work was found less than the present standard of the world but more than the standard of the country. A meta-analysis report of Mu et al, (14) confirmed that soy products significantly (p<0.05) reduced BMI of Asian populations (−0.27kg/m 2 ). Furthermore, Yamori (18) observed that feeding of fish in Japan was related to low BMI as soy feeding.…”
Section: Discussionmentioning
confidence: 88%
“…Akhlaghi and colleagues 32 thought soy showed no overall statistically significant effect on weight, WC or fat mass. However, Mu and colleagues 33 held that soy products significantly reduced body weight, BMI, body fat per cent and WC in overweight or obese Asian populations, and more significant effects were observed in non-menopausal women. Asbaghi and colleagues 34 found that magnesium supplementation did not affect body weight, BMI and WC, while Askari et al 35 found a significant reduction in BMI following magnesium supplementation and Rafiee et al 36 found that magnesium supplementation was associated with lower WC only in obese subjects.…”
Section: Discussionmentioning
confidence: 99%